The Characteristics of Children with Abnormalities Detected in Thyroid Function Tests, and Distribution of Diagnoses - Elif Çelik; Ayşe Anık (Galenos Publishing House, 2020)
INTRODUCTION: Thyroid function tests are among the most frequently implemented laboratory tests in primary, and secondary healthcare institutions. The aim of the present study was to investigate the demographic and clinical characteristics and final diagnosis of children referred by primary and secondary healthcare institutions with the suspicion of an abnormality in thyroid function test and/or with the initial diagnosis of specific thyroid disease. METHODS: A total of two hundred eighty-nine pediatric patients, aged between 4 and 18 years admitted to the outpatient clinics of Behçet Uz Children's Health and Diseases Hospital between January 2018 and January 2020, were included in the study. The patient data were obtained retrospectively from the hospital records. RESULTS: A total of 66% of the patients who were included in the study were female with a median age of 12 years (8.7-14.4), while 64% of them were pubertal; and 78% of the cases were referred by secondary healthcare institutions. The most common reason for referral was isolated elevation of thyroid stimulating hormone (TSH). A total of 56% of the patients were asymptomatic at the time of admission, and thyroid function test results of 75% of them were within normal limits. When evaluated according to their final diagnoses, the children were normal/healthy (64%), diagnosed with Hashimoto thyroiditis (30%), nodular thyroid disease (3%), Graves disease (2%) and isolated increase of TSH was related to obesity in 5 patients (1%). DISCUSSION AND CONCLUSION: It is essential to evaluate children with abnormal thyroid function test results with detailed history and physical examination. Besides, the thyroid function tests should be performed with reliable and sensitive methods in standardized laboratories to reach the correct diagnosis in these children.